InAs-mediated growth of vertical InSb nanowires on Si substrates - Li, Tianfeng (Springer, 2013)
In this work, InSb nanowires are grown vertically on Si (111) with metal organic chemical vapor deposition using InAs as seed layer, instead of external metal catalyst. Two groups of InSb nanowires are fabricated and characterized: one group presents Indium droplets at the nanowire's free end, while the other, in contrast, ends without Indium droplet but with pyramid-shaped InSb. The indium-droplet-ended nanowires are longer than the other group of nanowires. For both groups of InSb nanowires, InAs layers play an important role in their formation by serving as a template for growing InSb nanowires. The results presented in this work suggest a useful approach to grow catalyst-free InSb nanowires on Si substrates, which is significant for their device applications.